Technological and Social Drivers of Web 2.0 - Unold, Olgierd (Technologiczne i społeczne czynniki rozwoju Web 2.0, 2010)
The author identifies technological and social drivers and determinants of the second incarnation of the World Wide Web, i.e., Web 2.0. Born in 2004, this new phenomenon has been constantly gaining importance, to the extent of a perceived change of paradigm in the use of cyberspace. Six basic market drivers point to the new role of the user, whilst eight core patterns of Web 2.0 deal with both technological and social aspects of this new phenomenon. All those trends, patterns and forces are intertwined, creating an endless potential for both business and private applications of modern cyberspace. And recently the development has gone well beyond Web 2.0 – Semantic Web (Web 3.0) and Web Operating Systems (Web 4.0) epitomize the nearest future of the Web.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 267-275
Keywords: cyberspace; Web 2.0; social aspects; technological aspects